Combined modality therapy including cytoreductive surgery and heated intraperitoneal chemotherapy for synchronous low volume peritoneal carcinomatosis from adenocarcinoma of the tail of pancreas in a BRCA-2 carrier resulting in long-term disease-free survival: A case report. (June 2021) - Hoefer, Richard A.; Obiora, Chukwuemeka; Azab, Basem; Harden, Elizabeth A.; Kessler, John F.
Abstract: Introduction: A BRCA-2 mutation carrier with a metachronous pancreatic adenocarcinoma (PC) and established peritoneal metastases is presented. Combined modality therapy including Cytoreductive Surgery (CS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) was associated with long-term disease-free survival. Case presentation: A 62-yr. old female underwent successful treatment for stage IIIa carcinoma of the right breast at age 48. 11 years later a cystic adenocarcinoma of the tail of the pancreas with peritoneal metastases was diagnosed. Platin based neoadjuvant chemotherapy followed by definitive resection of the pancreatic mass with cytoreductive surgery (CS) and Hyperthermic Intraperitoneal Chemotherapy (HIPEC) with mitomycin C was performed. Postoperatively, a retro-gastric fluid collection developed from a pancreatic duct leak, successfully managed non-operatively. Maintenance poly ADP ribose polymerase (PARP) inhibitor therapy was initiated after recovery from surgery. The patient experienced a 30-month disease free survival and was subsequently found to have oligometastases to the brain. Discussion: CR and HIPEC have not been reported to be efficacious in patients with pancreatic carcinomatosis. However, PC arising in BRCA-2 carriers has a DNA repair defect, which is sensitive to platin based chemotherapy and mitomycin C. HIPEC has more severe postoperative complications following distal pancreatectomy. Isolated brain metastases from PC are rare. BRCA-2 mutation carriers are at significantly increased risk for PC. Conclusion: Leveraging the DNA Repair defect in BRCA-2 pancreatic adenocarcinoma, including CS and HIPEC, led to long-term disease-free survival and good locoregional control in this patient. Complications from HIPEC are more severe. BRCA-2 carriers should undergo annual pancreatic cancer screening. Highlights: BRCA-2 females should be considered for screening for pancreatic cancer. Pancreatic cancer in BRCA-2 mutation carrier has a defect in DNA repair. Accurate staging of pancreatic cancer is essential. CS and HIPEC can lead to good long-term control of abdominal disease. Complications from CS and HIPEC can be more severe but are manageable.